Oral metastasis of occult lung adenocarcinoma presenting as maxillary alveolar swelling: A case report - SUTHAR, PRAKRUTI VIJAY SUTHAR; Parikh, Dr. Shilpa; Joshi, Dr. Mruga; Shah, Dr. Jigna (Indian Journal of Case Reports, 2026)
Metastasis to the oral cavity from pulmonary malignancy is an exceptionally rare event, accounting for 1% of all oral malignancies. This report describes a unique case of a 66-year-old female in whom a destructive non-tender maxillary alveolar swelling served as a singular manifestation of an otherwise occult primary lung adenocarcinoma. The patient presented with a soft, non-tender swelling and a persistent sinus tract despite the extraction of teeth. Radiographs confirmed a 25×24×25 mm irregular mass causing complete erosion of the maxillary alveolus and floor of the right maxillary sinus. Diagnosis was established via biopsy and an immunohistochemical panel, which demonstrated co-positivity for thyroid transcription factor-1 and cytokeratin 7. This confirmed Stage IV disease, necessitating a transition to palliative care. The patient succumbed 2 months after diagnosis. This case underscores the necessity for clinicians to include distant metastasis in the diagnosis of non-healing or aggressive oral lesions, as timely identification is critical for appropriate staging and management.